Development and characterization of a stable adhesive bond between a poly(dimethylsiloxane) catheter material and a bacterial biofilm resistant acrylate polymer coating - Tyler, Bonnie J.; Hook, Andrew L.; Pelster, Andreas; Williams, Paul; Alexander, Morgan R.; Arlinghaus, Heinrich F. (American Vacuum Society, 2017)
Catheter associated urinary tract infections (CA-UTIs) are the most common health related infections world wide, contributing significantly to patient morbidity and mortality and increased health care costs. To reduce the incidence of these infections, new materials that resist bacterial biofilm formation are needed. A composite catheter material, consisting of bulk PDMS coated with a novel bacterial biofilm resistant polyacrylate (EGDPEA–co-DEGMA) has been proposed. The coated material shows excellent bacterial resistance when compared to commercial catheter materials but delamination of the coatings under mechanical stress presents a challenge. In this work, the use of oxygen plasma treatment to improve the wettability and reactivity of the PDMS catheter material and improve adhesion with the EGDPEA–co-DEGMA coating has been investigated. Argon Cluster 3D-imaging Time-of-Flight Secondary Ion Mass Spectrometry (ToF-SIMS) has been used to probe the buried adhesive interface between the EGDPEA–co-DEGMA coating and the treated PDMS. ToF-SIMS analysis was performed in both dry and frozen-hydrated states and results were compared to mechanical tests. From the ToF-SIMS data we have been able to observe the presence of PDMS, silicates, salt particles, cracks and water at the adhesive interface. In the dry catheters, low molecular weight PDMS oligomers at the interface were associated with poor adhesion. When hydrated, the hydrophilic silicates attracted water to the interface and led to easy delamination of the coating. The best adhesion results, under hydrated conditions, were obtained using a combination of 5 min O2 plasma treatment and silane primers. Cryo-ToF-SIMS analysis of the hydrated catheter material showed that the bond between the primed PDMS catheter and the EGDPEA–co-DEGMA coating was stable in the presence of water. The resulting catheter material was resisted Escherichia coli and Proteus mirabilis biofilm colonization by up to 95 % compared with uncoated PDMS after 10 days of continuous bacterial exposure and had the mechanical properties necessary for use as a urinary catheter.